2017
DOI: 10.1016/j.jgeb.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Improved micropropagation and in vitro fruiting of Morus indica L. (K-2 cultivar)

Abstract: A rapid economically viable micropropagation protocol has been developed in the present work for Morus indica L. (K-2 cultivar) utilizing the readily available nodal explants. Explants were established on different plant growth regulators (PGRs) either individually or in combinations. MS medium containing 1 mg L−1 Kinetin (Kin) showed the best shoot multiplication with 4.8 ± 0.23 cm average shoot length and 6.5 ± 0.03 number of internodes. Regenerated shoots were elongated in MS medium supplemented with 1.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…Also, a similar situation was also noticed by Santamaria (Pattnaik et al, 1996). On the other hand, Gogoi et al (Gogoi & Borua, 2017) reported that supplementation of the MS medium with 1.5 mg/l of gibberelic acid (GA 3 ) improved elongated shoots of Morus indica L. (K2-cultivar). Regarding rooting stage, it is well known that auxin regulates have various aspects of plant growth and development by affecting numerous processes including cell division, cell enlargement, and differentiation (Srivastava, 2002;Woodward & Bartel, 2005).…”
Section: Discussionsupporting
confidence: 67%
“…Also, a similar situation was also noticed by Santamaria (Pattnaik et al, 1996). On the other hand, Gogoi et al (Gogoi & Borua, 2017) reported that supplementation of the MS medium with 1.5 mg/l of gibberelic acid (GA 3 ) improved elongated shoots of Morus indica L. (K2-cultivar). Regarding rooting stage, it is well known that auxin regulates have various aspects of plant growth and development by affecting numerous processes including cell division, cell enlargement, and differentiation (Srivastava, 2002;Woodward & Bartel, 2005).…”
Section: Discussionsupporting
confidence: 67%
“…A high percentage of seed germination (90%) has been reported on sterile moistened filter paper or cotton in Petri dishes or test tubes in various crop species, including snake gourd (Pillai et al, 2008;Devendra et al, 2008 and; Brassica oleracea (Finch-Savage et al, 2006) and Triticum aestivum (Lehner et al, 2006) Ophiorrhiza mungos (Namdeo et al, 2012), Ipomoea sepiaria (Cheruvathur et al, 2015). In the present study, the higher regeneration efficiency was observed in leaf explants excised from 7-10 day-old seedlings (Gogoi et al, 2017), whereas in earlier reports cotyledon explants used were older than 3-4 days (Prem Kumar et al, 2015). Therefore, seeds were germinated on sterile moistened cotton and used for all the experiments in the present study.…”
Section: In Vitro Seedlingssupporting
confidence: 53%
“…The explant obtained in September was more susceptible to bacterial infection because of the high rate of rainfall (Vijayan et al 2011). Parental age also affects the contamination rate (Gogoi et al 2017). The older explant source was more susceptible to contamination.…”
Section: Initiationmentioning
confidence: 99%
“…The amount of light also supports flowering. The light plays a role as a sucrose regulator to induce florigen (Gogoi et al 2017).…”
Section: Initiationmentioning
confidence: 99%
See 1 more Smart Citation